Epidemiology of psoriasis in Italy: burden, cost, comorbidities and patients’ satisfaction. A systematic review - Gianfredi, Vincenza; Casu, Giulia; Bricchi, Lucia; Kacerik, Erika; Rongioletti, Franco; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: The Italian data on psoriasis are partial and, in most cases, come from monocentric studies, not representative of the population. Our aim was to conduct a systematic review of the available evidence in order to get the overall picture of the Italian epidemiology (prevalence and incidence); burden of disease (direct and indirect costs, the impact on quality of life); comorbidities; and finally, the patients’ satisfaction and acknowledgement of both the disease and the care services available. Methods: This systematic review followed the guidelines of the Cochrane Collaboration and the Prepared Items for Systematic Reviews and Meta-Analysis (PRISMA) 2020. The literature search was conducted on PubMed/Medline and Scopus. Results: Out of 387 retrieved articles, 41 were included in the analysis. Psoriasis is a frequent condition in Italy: the prevalence is between 1,8% and 4,8% and the incidence is between 107,742 and 230,62 per 100.000 person-years. The most frequent comorbidities associated to psoriasis are: diabetes, hypertension, obesity, depression, cardiovascular diseases, hypertriglyceridemia, and hypercholesterolemia. The quality of life and severity of the disease are mostly affected by other concurrent diseases, early onset of the disease, low income, and low level of education. The costs of psoriasis were estimated between 500 euro and 15.000 euro depending on the disease’s severity, the treatments used and hospitalization. Conclusions: In conclusion, psoriasis is a high-impact chronic disease. It is therefore fundamental to advocate a multidisciplinary approach to obtain a better health outcome, the patients’ management and the cost savings could benefit from it.